2019
DOI: 10.6017/ital.v38i3.11009
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of Open Access Finding Tools

Abstract: The open access (OA) movement seeks to ensure that scholarly knowledge is available to anyone with internet access, but being available for free online is of little use if people cannot find open versions. A handful of tools have become available in recent years to help address this problem by searching for an open version of a document whenever a user hits a paywall. This project set out to study how effective four of these tools are when compared to each other and to Google Scholar, which has long been a sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…It's also unclear if journalists are aware of the various routes to find green OA articles. Although several studies have shown Google Scholar and tools such as Unpaywall and Open Access Button make this relatively easy and effective, journalists would still need to first be aware of these discovery options (Martín-Martín et al, 2018;Schultz et al, 2019). Finally, some research is starting to show that more privileged scholarly authors -white men in senior positions at research institutions with known prestige and the resources to pay expensive publishing fees -are most likely to pay to publish OA, which almost always includes hybrid OA (Olejniczak & Wilson, 2020).…”
Section: Limitationsmentioning
confidence: 99%
“…It's also unclear if journalists are aware of the various routes to find green OA articles. Although several studies have shown Google Scholar and tools such as Unpaywall and Open Access Button make this relatively easy and effective, journalists would still need to first be aware of these discovery options (Martín-Martín et al, 2018;Schultz et al, 2019). Finally, some research is starting to show that more privileged scholarly authors -white men in senior positions at research institutions with known prestige and the resources to pay expensive publishing fees -are most likely to pay to publish OA, which almost always includes hybrid OA (Olejniczak & Wilson, 2020).…”
Section: Limitationsmentioning
confidence: 99%
“…Google Scholar searches websites that "consist primarily of scholarly articles-journal papers, conference papers, technical reports, or their drafts, dissertations, pre-prints, post-prints, or abstracts" and make abstracts or whole texts of articles available (Google Scholar, n.d.). With hundreds of millions of records, Google Scholar is the most comprehensive academic search engine available (Gusenbauer, 2019) and has been found to identify the most open-access articles of all search engines with a low rate of false positives (identifying an article as openly accessible when it is actually not; see Duffin, 2020;Gadd et al, 2019;Schultz et al, 2019).…”
Section: Finally You Might Skim Recent Issues Of Practitioner-focused...mentioning
confidence: 99%
“…Google Scholar is a powerful tool for finding scholarly articles that are openly accessible and we recommend using it as your first option. Although Google Scholar identifies most openaccess versions of peer-reviewed articles, it does not identify all (Schultz et al, 2019). Therefore, if an open-access version of an article you are looking for is not found in a Google Scholar search, it is worth trying alternative tools-such as Google, Lazy Scholar, and Open Access Button-to see if an open-access version exists that Google Scholar missed.…”
Section: Google Scholarmentioning
confidence: 99%